PENGARUH PENGGUNAAN MEDIA BIG BOOK DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II SD NEGERI TEPUNG SARI (JS (JURNAL SEKOLAH), 2025)
Abstract: Early reading skills are an important foundation in the development of student literacy at the elementary school level. This study aims to analyze the effect of using Big Book media in improving the early reading skills of second-grade students at Tepung Sari Elementary School. The method used was an experiment with a nonequivalent control group design. The research sample consisted of 30 students, who were divided into two groups: experimental and control. Data collection techniques included observation, documentation, and tests. The results of the analysis using the independent sample t-test showed a significance value of 0.000